Environmental Assessment of Water Quality in the Qarraoun Lake: The Investigation of PhysicoChemistry and Microbial Properties - Haydar, Chaden; Nehme, Nada; Kamar, Rime (European Scientific Journal, ESJ, 2019)
The Qarraoun Lake is the largest artificial reservoir in Lebanon, which is located along the Litani River in the Bekaa plain. It represents the connecting point between the Upper and Lower Litani River Basins. Water collected in the lake is used for multipurpose, and mainly for irrigation, fisheries, power generation, and domestic water use. Recently, the Lake has been witnessing severe deterioration in water quality due to uncontrolled liquid and soil waste disposal in the Upper River Basin. As a result, the pollutants accumulate into the Lake water. Apart from laboratory analysis for water quality, the pollution is obvious through direct observations, smells, and water color and patterns. This paper focuses on assessing the level of pollution in the Lake. Therefore, the physico-chemical and microbiological properties of water were investigated on 15 selected sampling on the representative sites of the Lake. Microbiological and physico-chemical analyses were performed in accordance with the European Standard Methods and World Health Organization (WHO). Multivariate statistical methods (Hierarchical Clustering Analysis: HCA, and Principal Component Analysis: PCA) were applied to figure out the influence of pollutants disposal in Qarraoun Lake. PCA was used to identify a reduced number of four principal components, which demonstrated 67.46 % of both temporal and spatial changes. CA shows that the Lake is divided into four clusters, where the central represent the most favorable one. Pollution index was used to classify the level of pollution of different sites in the Lake.